A qualitative study to explore views of patients, carers and mental health professionals' views on depression in Moroccan women. Issue 2 (3rd April 2018) - El Rhermoul, Fatema-Zahra; Naeem, Farooq; Kingdon, David; Hansen, Lars; Toufiq, Jallal
ABSTRACT: Moroccans make up a large immigrant population but no prior research has been carried out with them. This paper focused on understanding depression and its management among Moroccan women through exploration of their view of the cause, presentation and treatment of depression, as well as that of their carers and mental health professionals. This study was conducted in a Moroccan psychiatric hospital. Data was collected using audiotaped, semi-structured interviews carried out by psychiatrists, lasting 30 minutes. Participants included: (1) outpatients with a diagnosis of depression, (2) relatives of patients and (3) psychiatrists and psychologists. A total of 30 interviews were conducted in French/Arabic and translated into English. The analysis involved NVivo. The results highlight delayed presentations in the majority of patients and physical symptoms of depression with an emphasis on anger. Most patients and relatives ascribed depression to a social problem, with an emphasis on depleted patience. Patients' expectations of management depicted a bio-psycho-spiritual-social model of illness. Although half of all patients mentioned the evil eye as a potential cause, few saw traditional healers. Patient socioeconomic conditions and insufficient psychological training render psychotherapy an unexploited tool. This study reflects the importance of educating professionals with regards to diagnosis and therapy in non-Western cultures.